INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIPLE INTELLIGENCES DI SMAN 1 KEDUNGPRING LAMONGAN - Hepi Ikmal; Wiwit Sukaeni (Kuttab : Jurnal Ilmu Pendidikan Islam, 2021)
This paper attempts to describe and interpret Islamic religious education learning innovation based on Multiple Intelligences at SMAN 1 Kedungpring Lamongan. By using a qualitative descriptive approach and extracting data through interviews, observation and documentation. The results showed that the innovation of Islamic religious education learning based on Multiple Intelligences at SMAN 1 Kedungpring Lamongan was implemented through 4 (four) things. 1). Cultivating critical thinking through demonstration methods and role-playing in PAI learning and pre-test, 2). Learning that solves problems (problem-solving) with the use of ICT (Information and Communication of Technology) and learning outside the classroom by PAI teachers, 3). Learning that fosters creative thinking by choosing the correct method by the teacher and maintaining the atmosphere in the classroom, 4). communicative learning by conveying learning objectives and motivating students in learning.